2005
DOI: 10.2486/indhealth.43.133
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sleep Problems and Recent Life Events with Smoking Behaviors among Female Staff Nurses in Japanese Hospitals

Abstract: For the purpose of examining the relation of sleep problems and other possible correlates with smoking among staff nurses in hospitals, the cross-sectional data of a self-administered questionnaire survey for 522 Japanese female staff nurses were reanalyzed. Registered nurses or licensed practical nurses were 82%, while nursing assistants were 18%. The prevalence of current smoking (PCS) was 29%, being higher than that in the general population of Japanese women. The current smokers exhibited a high tendency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
3
25
1
2
Order By: Relevance
“…Regarding demographics, the average age of nurses in our study was slightly younger than the average age of female workers previously reported in Japan 33) , although the distribution of age groups was somewhat similar to that reported in the Japan Nurses' Health Study (JNHS) 34) . More than half the nurses were currently unmarried, which is similar to a previous Japanese study 35) . Few Japanese nurses in our investigation reported using OC, which is similar to a previous study from Taiwan where only two out of 907 nurses were current users 26) .…”
Section: Discussionsupporting
confidence: 77%
“…Regarding demographics, the average age of nurses in our study was slightly younger than the average age of female workers previously reported in Japan 33) , although the distribution of age groups was somewhat similar to that reported in the Japan Nurses' Health Study (JNHS) 34) . More than half the nurses were currently unmarried, which is similar to a previous Japanese study 35) . Few Japanese nurses in our investigation reported using OC, which is similar to a previous study from Taiwan where only two out of 907 nurses were current users 26) .…”
Section: Discussionsupporting
confidence: 77%
“…There were few studies that evaluated the relationship between shift work and cigarette smoking in Japanese female workers. Kageyama et al reported that the prevalenve of current smoker was 29%, being higher than that in the general population of Japanese women by evaluating 522 Japanese female staff nurses [9]. In this study, it is note worthy that we found the relationship between work style and cigarette smoking in women even after adjusting for age.…”
Section: Discussionsupporting
confidence: 51%
“…research targeting 736 two-shift workers and 1131 day workers at an oil refinery, and concluded that the 2-shift workers had higher job demand and less job control over their work [11]. In female workers, Kageyama et al reported that the cigarette smoking-dependent tendency was associated with recent life events and the presence of insomnia [9]. Stress is probably the most important contributor to excess smoking levels [12].…”
Section: Discussionmentioning
confidence: 99%
“…Night shift work has been associated with obesity, current smoking and smoking intensity 10,11) . Prospective data show a relation between going from standard to long work hours (LWH) and increased drinking in women, unhealthy weight gain for men and increased smoking (both genders) 12) .…”
Section: The Work Environment and Lrcrf: Mixed Findings With Generic mentioning
confidence: 99%